The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1557/jmr.2014.404
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation resistance of an early age slag-blended cement matrix for nuclear waste encapsulation

Abstract: Irradiation is one of the characteristic conditions that nuclear wasteforms must withstand to assure integrity during their service life. This study investigates gamma irradiation resistance of an early age slag cement-based grout, which is of interest for the nuclear industry as it is internationally used for encapsulation of low and intermediate level radioactive wastes. The slag cement-based grout withstands a gamma irradiation dose of 4.77 MGy over 256 hours without reduction in its compressive strength; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Formation of ettringite is considered to be desirable for nuclear waste encapsulation via cementation, as its large unit cell accommodates a high content of bound water, leaving less free water in the pore network available for radiolysis [10]. Radiolysis of free water compromises the integrity of a solid cement wasteform as it causes formation of cracks and open pores [11]. Ettringite can also act as a host for a number of both positively and negatively charged ions in both the columnar and channel sections, as isomorphous substituents within its structure [12].…”
Section: Introductionmentioning
confidence: 99%
“…Formation of ettringite is considered to be desirable for nuclear waste encapsulation via cementation, as its large unit cell accommodates a high content of bound water, leaving less free water in the pore network available for radiolysis [10]. Radiolysis of free water compromises the integrity of a solid cement wasteform as it causes formation of cracks and open pores [11]. Ettringite can also act as a host for a number of both positively and negatively charged ions in both the columnar and channel sections, as isomorphous substituents within its structure [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the dispersion of the data (around 10 % of standard deviation) does not lead to any statistical difference (t-test < 1 %). ATG analyses were performed on irradiated and pristine uncarbonated samples and no carbonation was observed [28]. To confirm this trend, experiments were reiterated on mortars as described in part 2.1.…”
Section: Mechanical Results On Cement Pastementioning
confidence: 92%
“…-2 ) and promote further formation of ettringite due to gamma exposure. Both Craeye et al (2015) and Mobasher et al (2015) confirmed formation of ettringite under gamma irradiation for a slag-rich blended cement mortar. Additionally, the strength of irradiated mortars with slag was not compromised with cracks and open voids formed as a result of radiolytic dehydration.…”
Section: Introductionmentioning
confidence: 73%
“…The heat is also generated in the specimens as a result of gamma irradiation (Reches 2019a). Also, the radiolysis of pore water, resulting in H 2 gas as a primary product and H 2 O 2 as a secondary product, is considered as the significant phenomenon (Bouniol and Aspart 1998), inducing spalling and micro-cracks in the cement matrix (Mobasher et al 2015). At high doses of gamma radiation an increased formation of calcite was observed (Vodak et al 2011) as a result of reaction of the radiolysis product H 2 O 2 with portlandite (Ca(OH) 2 ) to a reaction product that in presence of CO 2 is converted to CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%